2017
DOI: 10.1016/j.jpainsymman.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Professionals' Attitudes About Physician-Assisted Death: An Analysis of Their Justifications and the Roles of Terminology and Patient Competency

Abstract: Context Healthcare professionals (HCPs) are crucial to physician-assisted death (PAD) provision. Objectives To quantitatively assess the favorability of justifications for or against PAD legalization among HCPs, the effect of the terms “suicide” and “euthanasia” on their views, and their support for three forms of PAD. Methods Our questionnaire presented three cases: physician-assisted suicide, euthanasia for a competent patient, and euthanasia for an incompetent patient with an advance directive for eutha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
(62 reference statements)
1
11
0
3
Order By: Relevance
“…Internationally, a majority of the literature on assisted dying is focused on the physician; however, some research has also examined the roles of nurses and psychiatrists (Block & Billings, 1995;Edwards, 2016;Fujioka, Mirza, McDonald, & Klinger, 2018;Groenewoud et al, 1997;Schwarz, 1999). Much of this literature, however, is focused on opinions related to the ethics of assisted dying, and whether or not the practice is justifiable (Braverman, Marcus, Wakim, Mercurio, & Kopf, 2017;Glebock Gawor, & Ostrowski, 2013). Less explored is the experience of health care professionals working with patients, caregivers, and other providers through the process of MAiD.…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, a majority of the literature on assisted dying is focused on the physician; however, some research has also examined the roles of nurses and psychiatrists (Block & Billings, 1995;Edwards, 2016;Fujioka, Mirza, McDonald, & Klinger, 2018;Groenewoud et al, 1997;Schwarz, 1999). Much of this literature, however, is focused on opinions related to the ethics of assisted dying, and whether or not the practice is justifiable (Braverman, Marcus, Wakim, Mercurio, & Kopf, 2017;Glebock Gawor, & Ostrowski, 2013). Less explored is the experience of health care professionals working with patients, caregivers, and other providers through the process of MAiD.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding non-abandonment, a similar concern was also documented among Swiss palliative care physicians, who found it difficult to accompany patients in decision-making about assisted suicide while honouring palliative care principles that do not support this practice 11. Interestingly, the theme of non-abandonment figures among the reasons that US physicians provide for supporting the decriminalisation of euthanasia 29. Research in the Netherlands has shown that tension between what physicians consider to be a good death and patients’ views and preferences can have significant implications for the implementation of physician-assisted death 30.…”
Section: Discussionmentioning
confidence: 80%
“…Quanto à procedência dos artigos: 45,8% foram desenvolvidos em países da América do Norte 13,14,16,18,20,22,24,26,29,33,34 , 41,7% em países da Europa 15,17,21,23,25,[30][31][32]35,36 , 8,3% em países da América do Sul 27,28 e 4,2% em um país da Oceania 19 . Os países que mais publicaram sobre esta temática foram os Estados Unidos 13,14,16,18,20,22,24,26,29,33 , seguido por Portugal 17,21,25,32 e Bélgica 23,30,31,35 .…”
Section: Resultsunclassified
“…Oito estudos compuseram esta categoria e envolveram ações 15 e procedimentos 19 relacionados à abordagem e às condutas terapêuticas em idosos próximos do fim da vida, quando os sintomas são intratáveis e refratários. Observamse cuidados como a eutanásia 22,30,31 , a morte assistida 22,31 e a sedação paliativa 23,30,31,35,36 A abordagem ética nas condutas terapêuticas frente aos cuidados ao fim da vida envolve ações de escuta, diálogo, compaixão, solicitude e manutenção da esperança, dentro da relação de cuidados, respeitando o máximo possível o grau de autonomia e atendendo às necessidades espirituais do indivíduo 15 .…”
Section: Categoria 1: Condutas Terapêuticas Frente Aos Cuidados Ao Fiunclassified
See 1 more Smart Citation